Two new Pediopsis species and a new Ruandopsis species (Hemiptera: Cicadellidae: Macropsinae) from Madagascar - Yang, Liyuan; Dietrich, Christopher H.; Zhang, Yalin (Zootaxa, 2016)
Three new species, Pediopsis tripartita, P. subtilis and Ruandopsis elongata spp. nov., from Madagascar are described. These species represent the first records of their respective genera in Madagascar. Images of adults and genitalia of the three species are provided.